PERCEIVED EFFECTIVENESS OF PUNISHMENTS FOR FOREST OFFENCES (UUM Journal of Legal Studies, 2021)
The purpose of this paper is to determine if the law currently in force is ineffective and thus contributes to the occurrence of forest offences. The paper analyses the punishments under the National Forestry Act 1984 based on the perceptions of related stakeholders on the effectiveness of those punishments in addressing illegal logging and other forest offences. A questionnaire was utilized to obtain responses from 240 purposively selected stakeholders. The collected data were analysed in the context of measures of central tendency to identify the extent to which the respondents agreed with the stated items. The results demonstrate that the law wasgenerally perceived to be acceptable. The findings also identified compensation payment based on the value of tree or wood as themost significant item, while longer imprisonment term was rated as the least significant item.